Enhanced mitochondrial autophagy (mitophagy) in oligodendrocytes might play a role in white matter pathology in schizophrenia. (January 2020) - Bernstein, Hans-Gert; Keilhoff, Gerburg; Dobrowolny, Henrik; Steiner, Johann
Abstract: Disrupted white matter integrity is a typical feature of brain pathologic alterations in schizophrenia, which includes impaired myelination, decreased oligodendrocyte densities, distortion of their spatial distribution and deviations from normal oligodendrocyte cell morphology. While most genes expressed "in the remaining" oligodendrocytes are downregulated in schizophrenia, only a few are upregulated. To the latter group belong prohibitin 2 and DISC 1, which were recently identified as mitochondria-located mitophagy receptors. Their overexpression, together with greatly reduced numbers and densities of oligodendroglial mitochondria and the structurally "normal appearance of the remaining mitochondria" in these cells as reported by Uranova's group (Uranova et al., 2001, 2004, 2018), point to enhanced mitophagy in oligodendrocytes in schizophrenia, which is possibly even cell protective by preventing apoptosis. Since massive loss of white matter oligodendrocytes is a characteristic feature of schizophrenia, we assume that increased mitophagy is a late event in the development and/or further progression of white matter pathologic changes. Moreover, altered oligodendroglial mitophagy might in part result from antipsychotic treatment. Further studies are clearly needed to substantiate our hypothesis on enhanced mitochondrial autophagy in schizophrenia, whereby the "drug-naïve state" and the possible influence of antipsychotic treatment could be elegantly simulated using animal models of the disease.